A small CDC25 dual-specificity tyrosine-phosphatase isoform in Arabidopsis thaliana - Landrieu, Isabelle (National Academy of Sciences, 2004)
The dual-specificity CDC25 phosphatases are critical positive regulators of cyclin-dependent kinases (CDKs). Even though an antagonistic Arabidopsis thaliana WEE1 kinase has been cloned and tyrosine phosphorylation of its CDKs has been demonstrated, no valid candidate for a CDC25 protein has been reported in higher plants. We identify a CDC25-related protein (Arath;CDC25) of A. thaliana, constituted by a sole catalytic domain. The protein has a tyrosine-phosphatase activity and stimulates the kinase activity of Arabidopsis CDKs. Its tertiary structure was obtained by NMR spectroscopy and confirms that Arath;CDC25 belongs structurally to the classical CDC25 superfamily with a central five-stranded β-sheet surrounded by helices. A particular feature of the protein, however, is the presence of an additional zinc-binding loop in the C-terminal part. NMR mapping studies revealed the interaction with phosphorylated peptidic models derived from the conserved CDK loop containing the phosphothreonine-14 and phosphotyrosine-15. We conclude that despite sequence divergence, Arath;CDC25 is structurally and functionally an isoform of the CDC25 superfamily, which is conserved in yeast and in plants, including Arabidopsis and rice.